Factors Influencing the Audit Quality of Internal Supervisory Apparatus in the Binjai City Government - Fitri Mahyuni; Deliana Deliana (International Journal of Economics, Management and Accounting, 2024)
The quality of audits is a crucial measurement to determine how effectively an audit has been conducted and the extent to which it produces relevant, accurate, and reliable information. High-quality audit outcomes are typically assessed based on how well the audit team performs the planning process, ensures that the audit plan is relevant and effective, produces audit reports that meet stakeholders' needs, and adheres to ethical principles aligned with established auditing standards. This study aims to evaluate the extent to which several key factors—namely audit planning, audit implementation, audit reporting, and ethical principles—have a direct impact on the audit quality of the Government Internal Supervisory Apparatus (Aparat Pengawasan Intern Pemerintah, or APIP) in the Binjai City Government. The research employs a quantitative approach, utilizing primary data collected from a sample of 39 government auditors. Data analysis was performed using the SmartPLS (Partial Least Squares) application, which allows for the modeling of complex relationships between variables. The findings reveal that audit planning, audit implementation, and audit reporting all have a significant and direct influence on the quality of audit results. These components play a central role in enhancing the credibility, effectiveness, and usefulness of internal government audits. However, the study also finds that ethical principles, while essential in guiding professional conduct, do not have a statistically significant direct impact on audit quality in this specific context. The results underscore the importance of strengthening technical aspects of the audit process, such as planning and reporting, while also maintaining strong ethical foundations as complementary rather than primary determinants of audit quality. This research contributes to the ongoing efforts to improve the effectiveness and reliability of internal government audits in Indonesian public sector institutions.